Tratamento de efluente do beneficiamento da castanha de caju utilizando eletrocoagulação e oxidação eletroquímica - Costa, Patrícia Rachel Fernandes da (2018)
Industrial growth is a major cause of excessive pollution and release of chemical waste into water, atmosphere and soil. Contaminants released by the industry, such as lead, chromium and phenols, are considered to be very aggressive to nature and man and can cause permanent contamination and even the death of living beings. The industrial waste is distinguished by the quantity generated where much of it is classified as dangerous, ie class I waste, have characteristics such as: flammability, corrosivity, reactivity, toxicity and pathogenicity. The cashew nut processing industry (IBCC) generates a residue rich in phenolic compounds from the process of obtaining cashew nut (ACC) and cashew nut (LCC) liquid. The disposal or reuse of these effluents, without adequate treatment, can cause serious environmental and health problems, since they are mostly toxic and refractory to commonly used treatments. Requiring the use of more efficient treatment technologies, such as advanced electrochemical processes, among them there is electrocoagulation and electrochemical oxidation. In the process of electrochemical oxidation are produced • OH that are responsible for the degradation of recalcitrant organic compounds, in addition to having the advantage of not using chemical agents. The proposal of this thesis was divided in two articles, where in the first, a BDD-batch reactor with recirculation is used, for the first time, in the electrochemical treatment of a real cashew effluent. The following parameters were studied: pH, conductivity, current intensity and addition of electrolytes. The results clearly indicated that the addition of external electrolyte and initial pH change are two factors that do not lead to a significant improvement in organic matter degradation. On the other hand, an increase in current density promoted a COD removal of up to 89%, after 150 min of oxidation, due to the increase in the generation of strong oxidants. The low production of carboxylic acids has also been detected over time. The second article deals with a pioneering sequential process involving electrocoagulation (EC) and electrochemical oxidation (EO) approaches. The performance of the system was analyzed in terms of removal of chemical oxygen demand, by-product evolution, toxicity and energy consumption. Sequential experiments, using EC with 8.33 or 100 mA cm-2 plus EO, promoted COD removals of 51% and 80% respectively. Phytotoxicity analyzes were performed to evaluate the water quality for reuse in irrigation activities. Based on these results, the CE sequential experiment (8.33 mA cm-2 ) plus EO (35.5 mA cm-2 ) was considered the most efficient and feasible to purify the actual cashew processing effluent.